Improvement of bananas for black sigatoka and Panama disease resistance through genetic manipulation - Smet, K. de; Panis, Bartholomeus; Sagi, L.; Cammue, B.P.A.; Swennen, Rony L. (1994)
Bananas are a staple food in Eastern Africa, with 25.3% of the total world production. The production is, however, threatened by the presence of several diseases, of which the fungal diseases black sigatoka and Panama disease are the most important. With the development of embryogenic cell suspension cultures, the isolation of protoplasts there from and their successful regeneration, an invaluable vegetative material for genetic manipulation of bananas became available. The discovery of new types of antifungal proteins (ATP's) and the cloning of their encoding genes provide a source of resistance to fungal diseases that can be introduced into plant cells by genetic engineering.